Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/fib6030063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pitch-Based Short Carbon Fibers on the Workability, Unit Weight, and Air Content of Mortar Composite

Abstract: Pitch is a viscoelastic polymer material consisting of aromatic hydrocarbons. It is used to produce carbon fibers with sheet-like crystal structures. The aim of the work presented in this paper was to evaluate the effects of pitch-based short carbon fibers on the workability, unit weight, and air content of freshly mixed mortar composite. Experimental investigation was carried out on five different types of mortar composite, including a control mortar. Four mortar composites were prepared including pitch-based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…CFRM4, which included 4% carbon fibers, had a lower workability compared with CFRM1 and CFRM2, which had 1% and 2% carbon fibers, respectively. This is because the higher surface area of the carbon fibers tends to restrain the mobility of the fresh mortar composite [ 42 , 56 ] due to increased water demand to entirely wet the constituent materials. Therefore, a comparatively high superplasticizer dosage was required to make CFRM4 workable.…”
Section: Test Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CFRM4, which included 4% carbon fibers, had a lower workability compared with CFRM1 and CFRM2, which had 1% and 2% carbon fibers, respectively. This is because the higher surface area of the carbon fibers tends to restrain the mobility of the fresh mortar composite [ 42 , 56 ] due to increased water demand to entirely wet the constituent materials. Therefore, a comparatively high superplasticizer dosage was required to make CFRM4 workable.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…Furthermore, the air content increased to a greater extent with the higher volume content of carbon fibers, as evident from Table 3 . This is because the presence of carbon fibers in the mortar impedes the movement of air voids to the surface during casting and compaction, thus entrapping them in the fresh composite [ 18 , 42 ]. However, it is evident from Table 3 that CFRM3 had the lowest air content.…”
Section: Test Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of short carbon fibers on the workability, unit weight and air content of blended mortar composite were evaluated by Safiuddin et al (2018), results showed that the overall effects of carbon fibers when the fiber volume per cent is higher than 3% lead to decreasing the workability and unit weight with higher entrapped air content (Safiuddin et al 2018).…”
Section: Introductionmentioning
confidence: 99%